Seven Pitfalls of Technical Analysis - Guglielmo Maria Caporale; Alex Plastun (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines the main drawbacks of technical analysis. Although this is widely used by practitioners, from an academic perspective it can only be seen as a form of "voodoo finance". In particular, it runs into the following pitfalls: Subjectivity; Doubtful assumptions; Unjustified algorithms; Low profitability; Data snooping; Statistically insignificant results; Unrealistic simplifications. The key conclusion is that it is high time that (self-fulfilling) technical analysis be replaced by more sophisticated time-series forecasting methods and models such as fractional integration, R/S analysis and autoregressive specifications .
Keywords: C63; D84; E37; G12; 330; technical analysis; data snooping; financial markets; price forecasting; trading